Numerical investigation of three-dimensional bubble column flows: A detached eddy simulation approach - Masood, Rao Muhammad Atif; Delgado, Antonio (Chemical Engineering & Technology, 2014)
Numerical simulations were performed employing detached eddy simulation (DES) in a three-dimensional transient Euler-Euler framework for bubble columns, and all the computational fluid dynamics results were compared with a k-εlunate model and available experimental data. The numerical results are in good agreement with the experiments in predicting the time-averaged axial velocity and turbulent kinetic energy profiles. The flow-resolving capabilities of the DES model are highlighted, and it is shown that the DES turbulence model can be efficiently used for simulating flow field and turbulent quantities in the case of bubble columns.
UnivIS-Import:2018-02-22:Pub.2014.tech.ITC.stmmec.numeri_5
Keywords: Bubble column; Computational fluid dynamics; Detached eddy simulation; Turbulence models